Assessing the Performances of a Cultural Institution through Non-Financial Key Performance Indicators - Ilie, Cosmin (Acta Universitatis Danubius. Œconomica, 2022)
This article aims to apply the Balanced Scorecard performance measurement tool to evaluate the activity of the Museum of History, Culture and Christian Spirituality from the Lower Danube, through indicators of a non-financial nature, grouped in three perspectives: educational, stakeholder satisfaction and organizational development. The Balanced Scorecard Designer software validates the fact that the Museum of Christian History, Culture and Spirituality from the Lower Danube is a museum that recorded high performance during the evaluated period, namely the first six months of the current year. The usefulness of this managerial tool has been proven in practical application, and the results obtained will stimulate the efficiency of resources, in order to redirect them for the improvement of organizational management on those sectors that recorded lower values.